Reinterpreting Muhammadiyah’s Purification and Its Implications for the Educational Philosophy - Azaki Khoirudin; Qaem Aulassyahied (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
This article mainly explores the changing and development of thought that occurred in one of the largest modernist Islamic organizations in Indonesia, Muhammadiyah, regarding Islamic purification. Using intellectual history as an approach, this research concluded that even though Muhammadiyah had purification as its main characteristic, in fact it had its own reinterpretation being extended and expanded. By implementing Abdolkarim Soroush’s theory of contraction and expansion of religious knowledge, this research found that in the very early days of its inception, Muhammadiyah constructed its concept of purification from the spiritualization, rationalization, and functionalization of Islamic teachings. But after the inception of Tarjih division in 1927, the purification in Muhammadiyah had a narrower orientation from worships and creeds (puritanism) to the muamalah of world affairs (ultra-puritanism). Beginning in 1995, there was a wider scope in which the Tarjih division in Muhammadiyah expanded its issues of worship to include public and humanitarian issues; that era was called post-puritanism. Based on the core hypothesis that any changes in religious thought have implications for educational orientation, from George R. Knight’s perspective, several educational implications are obtained: (1) In the early days of its inception, Muhammadiyah’s education implemented a progressivism philosophy that’s inspired by religion, rationality, and life; (2) when it comes to the narrower aspect of purification only for faith, worship, and muamalah, Muhammadiyah shifted its educational philosophy to perennialism-essentialism; (3) when the purification's meaning and interpretation expanded, Muhammadiyah tended its education toward the philosophy of reconstructionism.